Wild logging: the rise and fall of logging networks and biodiversity conservation projects on Sumatra’s rainforest frontier - McCarthy, J.F. (Center for International Forestry Research, 2000)
During 1999-2000, the illegal and unregulated logging of Indonesia’s forests became the focus of critical attention. It has been estimated that logging outside the State legal regime produces approximately half of the total timber production from Indonesia’s forests. In 2000, as Indonesia’s forests continued to rapidly recede, the problem had become so critical that, without serious changes, the World Bank and other foreign donors considered withdrawing entirely from forestry sector projects in Indonesia. While on a national scale the extent of the problem is now understood, insufficient attention has been paid to how this ‘informal sector’ operates at the district level. The paper is based on research carried out in the district of South Aceh during 1996-1999, before and during the crisis that marked the end of the Suharto era. By considering the emergence of logging networks in this district, this paper examines the institutional arrangements associated with this phenomenon, explores how logging networks emerge, how they operate, and how they respond to economic and political changes as well as interventions by outside conservation agencies. Webs of political, economic and social exchanges have emerged around illegal logging, constituting institutionalised sets of relationships that operate in ways antithetical to State legal norms. Extra-legal logging generates revenue for local clientele networks and the district budget and offers impoverished villagers viable survival strategies, but threatens the ecological future of Indonesia’s once vast forests. By considering the changes that most affected logging networks over this period, the paper concludes by discussing the conditions necessary for successful project interventions.